2019
DOI: 10.1071/cp18546
|View full text |Cite
|
Sign up to set email alerts
|

Minerals in pastures—are we meeting the needs of livestock?

Abstract: In Australia, ruminants rely on introduced pastures or native vegetation for most or all of their nutritional requirements. Recent pasture selection and breeding programs have focused on improving or facilitating the establishment, persistence and growth of plants, with little emphasis on nutritive value or mineral composition. In some cases, such as selection for phosphorus (P) utilisation efficiency, mineral supply from plants may even decrease. Currently, a significant proportion of pasture plants contain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 73 publications
0
29
0
1
Order By: Relevance
“…Mineral composition of forages is of interest from a perspective of livestock health and, as with nutritive traits overall, there has been little or no emphasis on selection for mineral composition in forage breeding programs (Masters et al 2019). Significant family variation was observed for all minerals in this study, with relatively low influence of family-by-location interactions, moderate to high heritability and genomic prediction models with predictive abilities high in comparison to the other nutritive quality traits assessed (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Mineral composition of forages is of interest from a perspective of livestock health and, as with nutritive traits overall, there has been little or no emphasis on selection for mineral composition in forage breeding programs (Masters et al 2019). Significant family variation was observed for all minerals in this study, with relatively low influence of family-by-location interactions, moderate to high heritability and genomic prediction models with predictive abilities high in comparison to the other nutritive quality traits assessed (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Mineral composition of forages is of interest from a perspective of livestock health and, as with 519 nutritive traits overall, there has been little or no emphasis on selection for mineral composition in 520 forage breeding programs (MASTERS et al 2019). Significant genotypic variation was observed for all 521 minerals in this study, with relatively low influence of G x E, moderate to high heritability and genomic 522 prediction models with predictive abilities high in comparison to the other nutritive quality traits 523 assessed (Figure 1).…”
Section: Predictive Ability For Nutritive Traits 330mentioning
confidence: 99%
“…This is in contrast to many earlier studies where sheep and cattle offered vegetative wheat, showed an increase in LWG when minerals were supplemented (Dove and Mcmullen 2009;Bell and Dove 2012). Such discrepancy in LWG response to mineral supplementation was discussed in a recent review paper (Masters et al 2019), which highlighted that the use of mineral to be considered in conjunction with energy and CP supply in animal production. Based on the 'leaky bucket theory', deficiency in major nutrient supply (energy or CP) is the first limiting factor to animal performance rather than mineral deficiency.…”
Section: Discussionmentioning
confidence: 99%